A knowledge-based perception analysis about Biotechnology among university students in Bangladesh - Ali, Fariha Fatema (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.